2020
DOI: 10.1371/journal.pone.0229146
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation changes in temperate ombrotrophic peatlands over a 35 year period

Abstract: Global changes in climate and land use are occurring at an unprecedented rate, often triggering drastic shifts in plant communities. This study aims to reconstruct the changes that occurred over 35 years in the plant communities of temperate bogs subjected to indirect human-induced disturbances. In 2015-17, we resurveyed the vascular flora of 76 plots located in 16 bogs of southern Qué bec (Canada) first sampled in 1982. We evaluated changes in species richness, frequency of occurrence and abundance, while con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 72 publications
3
14
0
Order By: Relevance
“…In line with earlier work where it was suggested that changes in enviro–climatic conditions in peatland ecosystems lead to a significant turnover in the composition of the plant community (Robroek et al 2017), plant community composition was highly distinctive between sites. Moreover, our study confirms previous suggestions that enviro–climatic conditions are important drivers that underlie the composition of the vegetation, and that changes in these drivers result in alterations of the plant community (Gunnarsson et al 2002, Pinceloup et al 2020) and associated biotic interactions (Wiedermann et al 2007). Indeed, we note that site‐specificity of plant communities extends to the prokaryotic community, a pattern that is likely explained by the strong links between plant and microbial communities (Chronakova et al 2019, Ivanova et al 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with earlier work where it was suggested that changes in enviro–climatic conditions in peatland ecosystems lead to a significant turnover in the composition of the plant community (Robroek et al 2017), plant community composition was highly distinctive between sites. Moreover, our study confirms previous suggestions that enviro–climatic conditions are important drivers that underlie the composition of the vegetation, and that changes in these drivers result in alterations of the plant community (Gunnarsson et al 2002, Pinceloup et al 2020) and associated biotic interactions (Wiedermann et al 2007). Indeed, we note that site‐specificity of plant communities extends to the prokaryotic community, a pattern that is likely explained by the strong links between plant and microbial communities (Chronakova et al 2019, Ivanova et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…1). Hence, a turnover in the plant community as shown in earlier research (Gunnarsson et al 2002, Robroek et al 2017, Pinceloup et al 2020) will lead to complex changes in plant–microbe interactions that could affect ecosystem processes in the longer term (Morriën et al 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, our study confirms previous suggestions that enviro-climatological conditions are important drivers that underlie the composition of the vegetation, and that changes in these drivers result in alterations of the plant community (Gunnarsson et al 2002, Pinceloup et al 2020) and associated biotic interactions (Wiedermann et al 2007). Indeed, we note that site-specificity of plant communities is paralleled in the prokaryotic community, a pattern that is likely explained by the strong links between plant and microbial communities (Chronakova et al 2019;Ivanova et al 2020).…”
Section: Discussionsupporting
confidence: 90%
“…As these peatlands are situated in three distinct environmental zones (Metzger et al 2005) our data suggest that these networks are vulnerable to the effects of enviro-climatological change, and turnover at a faster rate than the individual biotic levels that comprise these networks. Hence, a turnover in the plant community as shown in earlier research (Gunnarsson et al 2002, Pinceloup et al 2020) will lead to complex changes in plant-microbe interactions that could affect ecosystem processes in the longer term (Morriën et al 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Peatlands in Europe and eastern and central Canada (0–60°E and 0–120°W; Figure 4g–l) are more productive than others (Figure 4g,h), while graminoids are more productive between 0–60°W and 120–180°E due to high moisture availability in near‐coastal environments (Figure 4i). Shrubs are the dominant plant type between 45 and 55°N due to high insolation and deeper WTP (Aerts et al, 1999; Pinceloup, Poulin, Brice, & Pellerin, 2020). In reality, many peatland areas are dominated by trees in such low latitudes, which is not represented in the model employed for this study, as there are challenges in dealing with the carbon produced by trees (Chaudhary et al, 2017a).…”
Section: Resultsmentioning
confidence: 99%